2012
DOI: 10.1021/es300897u
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Biodegradation of Carbamazepine after UV/H2O2 Advanced Oxidation

Abstract: Carbamazepine is one of the most persistent pharmaceutical compounds in wastewater effluents due to its resistance to biodegradation-based conventional treatment. Advanced oxidation can efficiently degrade carbamazepine, but the toxicity and persistence of the oxidation products may be more relevant than the parent. This study sets out to determine whether the products of advanced oxidation of carbamazepine can be biotransformed and ultimately mineralized by developing a novel methodology to assess these seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
59
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(61 citation statements)
references
References 27 publications
2
59
0
Order By: Relevance
“…Integrating advanced oxidation with bioremediation is a means to increase the biodegradability and water solubility of recalcitrant organic compounds, such as humics in natural waters, PAHs and organics in landfill leachate (Brame et al, 2013;Goi et al, 2006;Jung and Choi, 2003;Jung et al, 2005;Keen et al, 2012;Li et al, 2012;Rittmann et al, 2002;Wu et al, 2004), thus allowing microorganisms to mineralise the residuals.…”
Section: Introductionmentioning
confidence: 99%
“…Integrating advanced oxidation with bioremediation is a means to increase the biodegradability and water solubility of recalcitrant organic compounds, such as humics in natural waters, PAHs and organics in landfill leachate (Brame et al, 2013;Goi et al, 2006;Jung and Choi, 2003;Jung et al, 2005;Keen et al, 2012;Li et al, 2012;Rittmann et al, 2002;Wu et al, 2004), thus allowing microorganisms to mineralise the residuals.…”
Section: Introductionmentioning
confidence: 99%
“…UV only, UV/H 2 O 2 , and UV/TiO 2 ) can result to the removal of TrOCs through oxidative degradation [9,150], and also through the evaporation of volatile or semi-volatile TrOCs when temperature rises during UV irradiation [146,150]. It also has potential to enhance biodegradation by oxidising persistent TrOCs into smaller, more biodegradable products [147]. Varying TrOC removal has been observed depending on UV treatment conditions (Table 2) [9,146,147].…”
Section: Uv Oxidationmentioning
confidence: 99%
“…It also has potential to enhance biodegradation by oxidising persistent TrOCs into smaller, more biodegradable products [147]. Varying TrOC removal has been observed depending on UV treatment conditions (Table 2) [9,146,147]. Salihoglu et al [146] found that UV treatment caused only 15-21% removal of polycyclic aromatic hydrocarbons from sludge through volatilisation.…”
Section: Uv Oxidationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, CBZ has some effect on human embryonic cells, such as growth inhibition and morphological changes, even at a range environmental concentration of ng/L [18]. However, CBZ is one of the most persistent pharmaceuticals of concern in water and is resistant to both the conventional water treatment process and biodegradation [19]. Thus, advanced oxidation processes (AOPs) have become the important treatment methods in various waters [20].…”
Section: Introductionmentioning
confidence: 99%